Resilient skies: advancing climate-resilient UAVs for energy-efficient B5G communication in challenging environments - Saif, Abdu; Mohd Shah, Nor Shahida; Alnoamani, Aiman; Ameen, Ali; Curry, Edward; Al Khattat, Vailet Hikmat Faraj; Alsamhi, Saeed Hamood (2024)
Due to severe climatic circumstances exacerbated by climate change, deploying Beyond Fifth Generation (B5G) networks is critical. Unmanned Aerial Vehicles (UAVs) have become indispensable for B5G connectivity in inclement weather conditions such as snow, fog, and rain. This paper investigates energy-efficient B5G connectivity and climate-resilient UAVs. We evaluate the performance of UAV coverage and energy efficiency at different elevation angles under various weather conditions, including snow, fog, and rain. Additionally, we discuss the challenges environments and propose solutions to improve climateresilient and energy-efficient B5G communication. Emphasizing the adverse effects of climate change on communication networks, The paper’s findings highlight the significant impact of weather conditions on UAV coverage, B5G communication networks, and energy efficiency. This research paves the way for a more resilient and sustainable future.